Influence of Movement Restriction During the COVID-19 Pandemic on Uptake of DMPA-SC and Other Injectable Contraceptive Methods in Nigeria - Adefalu AA; Bankole OA; Olabode F; Afolabi MB; Buba MA; Dafe V; Kalu MN; Watkins E (Open Access Journal of Contraception, 2025)
Adewole Adebola Adefalu,1 Olufunke Abimbola Bankole,2 Funmilayo Olabode,2 Mojuba Bimbo Afolabi,2 Miranda Atare Buba,2 Victor Dafe,2 Mishael Nnanna Kalu,2 Emily Watkins3 1JSI Research & Training Institute, Inc., Atlanta, GA, USA; 2JSI Research & Training Institute, Inc., Abuja, FCT, Nigeria; 3JSI Research & Training Institute, Inc., Washington, DC, USACorrespondence: Adewole Adebola Adefalu, JSI Research & Training Institute, Inc., 437 Memorial Dr. SE Suite A11 − 2277, Atlanta, GA, 30312, USA, Tel +1 (678) 882-2797, Email calebadefalu2006@yahoo.comIntroduction: The COVID-19 pandemic caused significant disruptions to sexual and reproductive health (SRH) services globally, with a pronounced impact on low- and middle-income countries like Nigeria. This study investigates how COVID-19 travel restrictions influenced the uptake of depot medroxyprogesterone acetate subcutaneous (DMPA-SC) and other injectable contraceptives in Nigeria.Methods: This study analyzed 26 months of secondary logistics data from the national electronic Health Logistics Management Information System (e-HLMIS), covering 36 states and encompassing periods before, during, and after the implementation of travel restrictions. Statistical analyses, including one-way ANOVA and independent samples t-tests, were applied to assess trends in the consumption of DMPA-SC and compare them with other injectable contraceptives, such as intramuscular DMPA (DMPA-IM) and norethisterone enanthate (NET-EN).Results: Findings showed a significant increase in DMPA-SC consumption during the travel restriction period, with mean consumption rising from 57,187 units pre-restriction to 103,249 units during the restriction. This increase persisted post-restriction, with mean consumption reaching 124,561 units. While the use of other injectable contraceptives also rose during the pandemic, their growth did not sustain as consistently as DMPA-SC.Discussion: The results suggest that promoting self-administration of DMPA-SC was essential in maintaining contraceptive access when conventional healthcare services were disrupted. This study highlights the importance of adaptable healthcare delivery models, such as self-administration, in ensuring SRH service continuity during global crises. Additionally, it underscores the need for resilient supply chain management to secure contraceptive availability in emergencies, providing critical insights for policymakers and healthcare providers aiming to enhance SRH service resilience in future public health challenges.Plain language summary: The COVID-19 pandemic disrupted healthcare services globally, including in Nigeria, making it challenging for women to access family planning services. Many women in Nigeria rely on injectable contraceptives to prevent pregnancy, but pandemic-related travel restrictions and fears of the virus made it difficult to visit health clinics for these services.This study investigated how the pandemic influenced the use of injectable contraceptives, particularly DMPA-SC, a type of injectable contraceptive that women can self-administer at home. Researchers analyzed data from health facilities across Nigeria, covering 26 months that included periods before, during, and after COVID-19 travel restrictions. They compared the use of DMPA-SC with other injectables, like DMPA-IM and norethisterone enanthate (NET-EN), which require administration by a healthcare provider.The study found that more women began using DMPA-SC during the travel restrictions, likely due to its self-administration feature, which provided autonomy and convenience when clinic access was limited. Even after the restrictions were lifted, the use of DMPA-SC continued to grow, suggesting that many women preferred this method once they experienced its benefits. While the use of other injectables also increased during the pandemic, the rise in DMPA-SC use was more significant and sustained.These findings highlight the importance of offering self-administered contraceptives to ensure women can maintain control over their reproductive health during crises. They also emphasize the need for strong supply chains to make contraceptives consistently available. Supporting self-administered options like DMPA-SC empowers women and ensures continuous access to family planning, even during emergencies.Keywords: COVID-19, family planning, contraception, depot medroxyprogesterone acetate, injectable contraceptive methods